Degradable bio-based supramolecular adhesive as well as preparation method and application thereof

By using quaternary ammonium polysaccharides and sulfated polysaccharides to prepare bio-based supramolecular adhesives, the problems of complex preparation and use of toxic solvents in existing technologies have been solved. This has resulted in a high-strength, mildew-resistant, and widely applicable green adhesive suitable for a variety of substrates and extreme environments.

CN121471842APending Publication Date: 2026-02-06FUJIAN NORMAL UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511690002.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-11-18
Publication Date
2026-02-06

AI Technical Summary

Technical Problem

Existing bio-based adhesives suffer from problems such as complex chemical modification, use of toxic solvents, cumbersome raw material extraction, high cost, susceptibility to mold growth, and narrow pH range during preparation, making it difficult to achieve green, environmentally friendly, and high-strength bonding effects.

Method used

Using renewable quaternary ammonium polysaccharides and sulfated polysaccharides as raw materials, a bio-based supramolecular adhesive is prepared through a simple mixing and drying process, avoiding the use of organic solvents. It forms a supramolecular structure of quaternary ammonium polysaccharides and sulfated polysaccharides with opposite charges, has a wide applicable pH range, and possesses high bonding strength and anti-mildew properties.

Benefits of technology

The prepared adhesive has high bonding strength, good durability, excellent anti-mildew properties, wide applicability, and is biodegradable. It is suitable for a variety of substrates, can withstand extreme temperature and pH environments, and meets green and environmental protection requirements.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121471842A_ABST
    Figure CN121471842A_ABST
Patent Text Reader

Abstract

The invention discloses a degradable bio-based supramolecular adhesive as well as a preparation method and application thereof, and belongs to the field of bio-based adhesives. Raw materials of the bio-based supramolecular adhesive comprise quaternary ammonium salt polysaccharide and sulfated polysaccharide with opposite charges, and the method comprises the following steps: uniformly mixing aqueous solutions of bio-based polysaccharide with opposite charges, separating precipitates after self-assembly phase separation, and re-dispersing the precipitates in water to obtain a liquid glue type adhesive; and blade-coating the liquid adhesive to form a film, and drying to obtain the solid adhesive tape type adhesive. The bio-based supramolecular adhesive has the bonding strength of 1 MPa or above for base materials such as wood, ceramic, glass and stainless steel, has long-term stability in a wide temperature range of-196 DEG C to 80 DEG C, and has excellent tolerance to strong alkali and strong acid environments. In addition, the raw materials of the adhesive are renewable, the preparation process is simple, convenient and green, the adhesive can be rapidly biodegraded after being used, and the adhesive has the excellent environment-friendly characteristic.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of bio-based adhesives, specifically relating to a biodegradable bio-based supramolecular adhesive, its preparation method, and its application. Background Technology

[0002] Adhesives play a vital role in daily life and industrial production. Currently, the vast majority of adhesives are petroleum-based, posing environmental problems such as volatile organic compound (VOC) emissions, consumption of non-renewable resources, and difficult-to-degrade waste. In recent years, with increasingly stringent environmental protection requirements and the advancement of sustainable development strategies, bio-based adhesives, which are renewable, biodegradable, and low in toxicity, have become highly promising alternatives to petroleum-based adhesives.

[0003] Currently, most biodegradable bio-based adhesives reported in the literature use biomass and their derivatives such as proteins, vegetable oils, and polysaccharides as their main components. These raw materials are widely available, environmentally friendly, and have high practical application value. However, to improve the bonding strength and durability of bio-based adhesives, the preparation process often involves chemical modification and the use of large amounts of toxic and harmful solvents, making the process complex and inconsistent with green development requirements. In recent years, to improve the sustainability of bio-based adhesive preparation processes, developing novel bio-based adhesives using biomimetic methods has become a new research direction. Examples include biomimetic adhesives inspired by barnacle cement protein, mussel foot protein, and snail mucus. These biomimetic adhesives have relatively simple and environmentally friendly preparation processes, bringing new ideas to the development of bio-based adhesives. However, these biomimetic adhesives typically use proteins or peptides as the main active ingredients, which presents problems such as cumbersome raw material extraction or synthesis, high cost, susceptibility to mold growth, and a narrow pH range. Polysaccharides, as the most abundant biomass resource in nature, are widely available, diverse, and inexpensive. Furthermore, polysaccharide molecules are rich in functional groups and easily modified; for example, quaternized polysaccharides have advantages such as antibacterial and antifungal properties and a wide pH range. In addition, naturally derived sulfated polysaccharides, such as chondroitin sulfate and carrageenan, also have a wide pH range due to the very low pKa of their sulfate ester groups.

[0004] Therefore, it is necessary to develop a bio-based supramolecular adhesive based on quaternary ammonium polysaccharides and sulfated polysaccharides that combines a simple and green preparation process with high bonding strength, good durability, excellent anti-mildew properties, and a wide pH range. Summary of the Invention

[0005] In view of the above-mentioned shortcomings in the existing technology, the purpose of this invention is to provide a biodegradable bio-based supramolecular adhesive, its preparation method and application. The bio-based supramolecular adhesive uses renewable quaternary ammonium salt polysaccharides and sulfated polysaccharides as raw materials. The preparation method is green and environmentally friendly, the process is simple and does not involve the use of organic solvents. The adhesive has the characteristics of high bonding strength, good durability, excellent anti-mildew properties and wide pH range.

[0006] To achieve the above objectives, the present invention provides the following technical solution:

[0007] In a first aspect, the present invention provides a biodegradable bio-based supramolecular adhesive, the raw materials for which the preparation includes quaternary ammonium salt polysaccharides and sulfated polysaccharides; the bio-based supramolecular adhesive is prepared from quaternary ammonium salt polysaccharides and sulfated polysaccharides with opposite charges.

[0008] Furthermore, the quaternary ammonium salt polysaccharide is chitosan quaternary ammonium salt, and the sulfated polysaccharide is one or more of chondroitin sulfate, k-carrageenan, l-carrageenan, and λ-carrageenan.

[0009] Preferably, the adhesive raw materials include chitosan quaternary ammonium salt and chondroitin A sodium salt.

[0010] Furthermore, the degradation bio-based supramolecular adhesive exhibits a mass loss rate of ≥95% after 20 days in natural soil at 20 °C~30 °C and 75%~95% humidity.

[0011] Secondly, the present invention provides a method for preparing a biodegradable bio-based supramolecular adhesive, the method comprising the following steps:

[0012] Step 1: Prepare aqueous solutions of quaternary ammonium salt polysaccharides and sulfated polysaccharides with charge concentrations ranging from 1 mM to 200 mM, respectively;

[0013] Step 2: Mix the two solutions evenly with a positive to negative charge ratio of 1:0.1 to 1:10, and control the pH of the mixture at 1 to 14.

[0014] Step 3: Centrifuge the mixed solution from Step 2 to separate the precipitate;

[0015] Step 4: Redisperse the precipitate in water by mechanical stirring or ultrasonic dispersion to obtain a liquid adhesive.

[0016] Step 5: Apply the liquid adhesive from Step 4 into a film and dry it at room temperature or at a temperature below 80 °C to obtain a solid tape adhesive.

[0017] The preferred technical solution is as follows: In step 1, the charge concentration of the aqueous solution of quaternary ammonium polysaccharide and sulfated polysaccharide is preferably 10 mM to 100 mM.

[0018] The preferred technical solution is as follows: In step 2, the positive and negative charge ratio of the quaternary ammonium polysaccharide and the sulfated polysaccharide is preferably 1:0.5 to 1:10, and more preferably 1:1 to 1:2; the pH of the mixture is preferably 4 to 14.

[0019] The preferred technical solution is as follows: In step 4, the dispersion process of the liquid adhesive is mechanical stirring or ultrasonic dispersion, and the solid content of the prepared liquid adhesive is 5wt.%-30wt.%.

[0020] The preferred technical solution is as follows: In step 5, after the liquid adhesive is coated into a film, it is heated and dried at 60 °C for 1 h, or the film-forming process of the solid tape adhesive is dried at room temperature or heated and dried at a temperature below 80 °C to obtain the solid tape adhesive.

[0021] Thirdly, this invention provides an application of a biodegradable bio-based supramolecular adhesive. When coated or pasted onto substrates such as wood, ceramics, glass, stainless steel, nylon, and synthetic stone, it can achieve a bonding strength ≥1 MPa. The bonding strength of the substrate after aging for 2 months in a temperature range of -196 °C to 80 °C is ≤10%. The bonding strength after soaking in an aqueous solution with pH=4-14 for 24 hours and drying is ≥3 MPa. The bonding strength after soaking in a strongly acidic aqueous solution with pH=1 for 24 hours and drying is still greater than 1 MPa.

[0022] The present invention has the following beneficial effects:

[0023] (1) The adhesive raw material described in this invention is a renewable biomass resource, which has the characteristics of wide availability and low price.

[0024] (2) The adhesive preparation method described in this invention is green and environmentally friendly, simple in process and does not involve organic solvents, has high repeatability and is easy to mass-produce.

[0025] (3) The adhesive described in this invention has a wide range of applications, high bonding strength to a variety of substrates, excellent durability at extreme low temperatures (-196 °C) and high temperatures (80 °C), good tolerance to strong alkaline and strong acid environments, and also has good anti-mildew properties.

[0026] (4) The adhesive described in this invention is biodegradable and has the characteristics of being green, environmentally friendly, non-toxic and harmless. Attached Figure Description

[0027] Figure 1 The adhesion strength diagram of the adhesive-type adhesive provided in Example 1 on various substrates;

[0028] Figure 2The diagram shows the anti-mildew performance of the adhesive-type binder provided in Example 1;

[0029] Figure 3 This is a diagram showing the adhesive strength of the tape-type adhesive provided in Example 2 on various substrates;

[0030] Figure 4 The graph shows the change in mass loss over time of the tape-type adhesive provided in Example 2 in natural soil.

[0031] Figure 5 The adhesive strength diagram of the adhesive provided in Example 3 at different raw material concentrations;

[0032] Figure 6 The adhesive strength diagrams for the adhesive provided in Example 4 at different proportions;

[0033] Figure 7 The adhesive strength diagram of the adhesive provided in Example 5 at different pH values;

[0034] Figure 8 The adhesive strength diagram of the adhesive provided in Example 6 after being placed at different temperatures for 2 months;

[0035] Figure 9 The adhesive strength diagrams for the adhesive provided in Example 7 after soaking for 24 hours at different pH levels and then drying are shown. Detailed Implementation

[0036] The technical solution of the present invention will be described below with reference to the accompanying drawings and embodiments. It should be emphasized that the provided embodiments are merely illustrative and do not constitute any limitation on the present invention; the scope of protection of the present invention is uniquely defined by the claims.

[0037] All reagents used in the embodiments of this invention can be purchased commercially.

[0038] The specific embodiments of the present invention are as follows:

[0039] A biodegradable bio-based supramolecular adhesive, its preparation method and application

[0040] Example 1

[0041] This embodiment provides a method for preparing a glue-type adhesive, the specific steps of which are as follows:

[0042] 3.9152 g of chitosan quaternary ammonium salt and 6.2423 g of chondroitin sulfate were dissolved in 250 mL of ultrapure water to prepare chondroitin sulfate solution and chitosan quaternary ammonium salt solution with a charge concentration of 50 mM, respectively. 10 mL of each solution was taken and thoroughly mixed in a 1:1 ratio of positive to negative charge. The mixture was centrifuged at 10000 r / min for 1 minute to separate the precipitate containing a large amount of water. The precipitate was stirred evenly to obtain a liquid adhesive. The liquid adhesive was applied to bamboo, wood, glass, stainless steel, synthetic stone, and nylon substrates, with 0.05 mL / cm² applied to each sample. 2 The adhesive was applied to a bonding area of ​​1 cm × 1 cm. Initial curing was performed by pressing for 10 seconds, followed by 12 hours of resting at room temperature for complete curing. The cured substrate was then subjected to a universal tensile testing machine to test the bond strength. During the tensile test, the stretching rate was 5 mm / min. A complete test was performed when the two materials were completely separated. A total of three tests were conducted, and the average value was taken.

[0043] The bonding strength of the liquid adhesive described in this embodiment to different substrates (bamboo, wood, glass, stainless steel, synthetic stone, nylon) is as follows: Figure 1 As shown, this adhesive exhibits excellent bonding strength to various substrates, especially on wood (bamboo), where it can achieve a bonding strength of over 3 MPa. When this adhesive-type binder is placed under conditions of 90±2% relative humidity and 28±2 °C, [the following is a separate, unrelated sentence:] Figure 2 It can be seen that the adhesive did not develop mold within 1 month.

[0044] Example 2

[0045] This embodiment provides a method for preparing a tape-type adhesive, the specific steps of which are as follows:

[0046] 3.9152 g of chitosan quaternary ammonium salt and 6.2423 g of chondroitin sulfate were dissolved in 250 mL of ultrapure water to prepare chondroitin sulfate solution and chitosan quaternary ammonium salt solution with a charge concentration of 50 mM, respectively. 10 mL of each solution was taken and thoroughly mixed in a 1:1 ratio of positive to negative charge. The mixed solution (pH=7) was placed in a centrifuge and centrifuged at 10000 r / min for 1 minute to separate the precipitate containing a large amount of water. 5 g of water was added to the precipitate, and after stirring evenly, the mixture was coated into a film and dried at 60 °C for 1 h to obtain a solid tape-type adhesive with a thickness of 0.1-2 mm. The solid tape-type adhesive was moistened with water and then adhered to bamboo, wood, glass, stainless steel, synthetic stone, and nylon substrates. The adhesion area of ​​the adhesive on each sample was 1 cm × 1 cm. Preliminary curing was performed by pressing for 10 s, followed by complete curing at room temperature for 12 h. The bond strength of the cured substrate was tested using a universal tensile testing machine. The tensile rate was 5 mm / min. The test was completed when the two materials were completely separated. The test was repeated 3 times and the average value was taken.

[0047] The adhesive tape described in this embodiment exhibits the following bonding strengths to different substrates (bamboo, wood, glass, stainless steel, synthetic stone, nylon): Figure 3 As shown, this solid tape adhesive exhibits excellent bonding strength to various substrates, particularly achieving a bonding strength of 3 MPa on wood (bamboo). When placed in natural soil at 20°C–30°C and 75%–95% humidity, the adhesive... Figure 4 It can be seen that the quality loss rate of the adhesive after 20 days is over 95%.

[0048] Example 3

[0049] The preparation method of the adhesive described in this embodiment is the same as that in Example 1, except that the charge concentrations of the chondroitin sulfate solution and the chitosan quaternary ammonium salt solution are both 20 mM. Specifically, 1.5661 g of chitosan quaternary ammonium salt and 2.4969 g of chondroitin sulfate are dissolved in 250 mL of ultrapure water to prepare the chondroitin sulfate solution and chitosan quaternary ammonium salt solution with charge concentrations of 20 mM. Other dosages, preparation methods, and testing methods are the same as in Example 1, and the test substrate is bamboo and wood.

[0050] The adhesive-type bonding strength of the adhesive to bamboo and wood described in this embodiment is as follows: Figure 5 As shown, this adhesive-type binder exhibits excellent bonding strength at different raw material concentrations.

[0051] Example 4

[0052] The preparation method of the adhesive described in this embodiment is the same as that in Example 1, except that the positive and negative charge ratio of the chitosan quaternary ammonium salt and chondroitin sulfate mixed solution is 1:2. That is, 10 mL of 50 mM chitosan quaternary ammonium salt solution and 20 mL of 50 mM chondroitin sulfate solution are taken and mixed evenly to prepare a glue-type adhesive. Other dosages, preparation methods and testing methods are the same as in Example 1, and the test substrate is bamboo and wood.

[0053] The adhesive-type bonding strength of the adhesive to bamboo and wood described in this embodiment is as follows: Figure 6 As shown, this adhesive exhibits excellent bonding strength at different ratios of chitosan quaternary ammonium salt and chondroitin sulfate.

[0054] Example 5

[0055] The preparation method of the adhesive described in this embodiment is the same as that in Example 1, except that the pH of the mixed solution of chondroitin sulfate and chitosan quaternary ammonium salt is 14, that is, the pH of the mixed solution is adjusted to 14 with sodium hydroxide. Other dosages, preparation methods and testing methods are the same as in Example 1, and the test substrate is bamboo and wood.

[0056] The adhesive-type bonding strength of the adhesive to bamboo and wood described in this embodiment is as follows: Figure 7 As shown, the bamboo exhibits excellent bonding strength with adhesives of different pH values.

[0057] Example 6

[0058] The method for testing the adhesive bonding strength described in this embodiment is the same as that in Example 1, except that after the adhesive has cured the substrate, it is placed at -196 °C, -25 °C, 25 °C, 60 °C, and 80 °C for two months, respectively, and then the bonding strength is tested after it returns to room temperature. Other dosages, preparation methods, and testing methods are the same as in Example 1, and the test substrate is bamboo or wood.

[0059] The bonding strength of the adhesive-type adhesive described in this embodiment on bamboo and wood after aging at different temperatures for 2 months is as follows: Figure 8 As shown, this adhesive demonstrates excellent durability under extreme temperatures.

[0060] Example 7

[0061] The method for testing the adhesive bonding strength described in this embodiment differs from that in Example 1 in that, after the adhesive-bonded substrate has cured, it is immersed for 24 hours in hydrochloric acid aqueous solutions with pH 1 and 4, pure aqueous solution with pH 7, and sodium hydroxide aqueous solutions with pH 10 and 14, respectively, and then dried before testing the bonding strength. Other dosages, preparation methods, and testing methods are the same as in Example 1, and the test substrate is bamboo or wood.

[0062] The bonding strength of the adhesive-type adhesive described in this embodiment on bamboo and wood after soaking in aqueous solutions of different pH values ​​for 24 hours and then drying is as follows: Figure 9 As shown, this adhesive demonstrates its resistance to strong alkaline and acidic environments.

[0063] Specific embodiments of the present invention have been described in detail above, but these embodiments are merely examples. The scope of the present invention is not limited to the specific embodiments described above. For those skilled in the art, any equivalent modifications and substitutions to the present invention fall within the scope of protection of the present invention. Therefore, any equivalent transformations and modifications made to the present invention that do not depart from the spirit and basic principles of the present invention should be covered within the scope of the present invention.

Claims

1. A biodegradable bio-based supramolecular adhesive, characterized in that, The bio-based supramolecular adhesive is prepared from quaternary ammonium salt polysaccharides and sulfated polysaccharides with opposite charges.

2. The biodegradable bio-based supramolecular adhesive according to claim 1, characterized in that, The quaternary ammonium salt polysaccharide is chitosan quaternary ammonium salt, and the sulfated polysaccharide is selected from one or more of chondroitin sulfate, k-carrageenan, l-carrageenan or λ-carrageenan.

3. The biodegradable bio-based supramolecular adhesive according to claim 1, characterized in that, The degradation bio-based supramolecular adhesive exhibits a mass loss rate of ≥95% after 20 days in natural soil at 20 °C~30 °C and 75%~95% humidity.

4. A method for preparing a biodegradable bio-based supramolecular adhesive according to any one of claims 1-3, characterized in that, Includes the following steps: Step 1: Prepare aqueous solutions of quaternary ammonium salt polysaccharide and sulfated polysaccharide respectively; Step 2: Mix the two aqueous solutions from Step 1 evenly; Step 3: Centrifuge the mixed solution obtained in Step 2 to separate the precipitate; Step 4: Disperse the precipitate evenly in water to obtain a liquid adhesive. Step 5: Apply the liquid adhesive obtained in Step 4 into a film and dry it to obtain a solid tape adhesive.

5. The preparation method according to claim 4, characterized in that, The initial charge concentration of the aqueous solutions of quaternary ammonium polysaccharides and sulfated polysaccharides ranged from 1 mM to 200 mM.

6. The preparation method according to claim 4, characterized in that, The positive and negative charge ratio of the aqueous solutions of quaternary ammonium polysaccharides and sulfated polysaccharides is 1:0.1 to 1:

10.

7. The preparation method according to claim 4, characterized in that, The pH value of the mixed solution of quaternary ammonium polysaccharide and sulfated polysaccharide is 1~14.

8. The preparation method according to claim 4, characterized in that, The dispersion process of the liquid adhesive described in step 4 is mechanical stirring or ultrasonic dispersion, and the solid content of the prepared liquid adhesive is 5wt.%-30wt.%.

9. The preparation method according to claim 4, characterized in that, The film-forming process of the solid tape adhesive described in step 5 is either room temperature drying or heating drying at a temperature below 80 °C.

10. The application of a biodegradable bio-based supramolecular adhesive according to any one of claims 1-3 or a biodegradable bio-based supramolecular adhesive prepared by any one of claims 4-9, characterized in that, The bio-based supramolecular adhesive exhibits bonding strengths ≥1 MPa to wood, ceramics, glass, stainless steel, nylon, and synthetic stone. Furthermore, the bonding strength decay rate after aging for 2 months within a temperature range of -196 °C to 80 °C is ≤10%, and the bonding strength after soaking in an aqueous solution with pH=4-14 for 24 hours and then drying is ≥3 MPa.